International differences in industrial structure; eight nations in the 1950s - Bain, Joe Staten (New Haven London : Yale University Press, 1966)
This provides a comparative industrial organization of countries or national economies, dealing with their industrial structures and the economic performance of their industries. The comparison includes: non-agricultural industries, manufacturing, distributive trades, service trades, public utilities and urban industries. The countries compared include: the United States, Canada, the United Kingdom, Sweden, France, India and Japan.
Includes bibliographical references: p. 183-200.
lje 14/05/2018
Loans
Keywords: Industrial organization (Economic theory); Manufactures; Comparative economics